PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN TORSO TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM PENCERNAAN PADA MANUSIA DI SMP NEGERI 19 PALEMBANG - Muhammad Isnaini; Indah Wigati; Resti Oktari (Biota, 2015)
The problem of education and teaching is a fairly complex problem in which many factors that come into effect. One of these factors include instructional media. Phenomena that occur in the field in teaching and learning activities are still centered on the teacher, student activities monotonous, many students receive the teacher's explanation, and student learning outcomes obtained unfavorable. The problem in this research is how to use instructional media torso toward student learning outcomes and whether there is influence learning media usage torso toward student learning outcomes. On the subject of human digestive system in SMP Negeri 19 Palembang held on July 27, 2015 until August 14, 2015. The purpose of the study is to examine the use of learning media torso toward student learning outcomes on the material in the human digestive system in SMP Negeri 19 Palembang , which includes planning, implementation, and evaluation, as well as to determine the effect of the use of learning media torso toward student learning outcomes on the material in the human digestive system in SMP Negeri 19 Palembang. The method in this research is quantitative experiments using t-test analysis. Posttest value analysis results obtained thitung price > ttable or 3.193 > 2.66. This indicate that the rejected Ha Ho accepted that hypothesis states that "There is the influence of the use of learning media torso toward student learning outcomes on the material in the human digestive system in SMP Negeri 19 Palembang".